PENDEKATAN LABIRIN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF DAN MENDAPATKAN GAMBARAN MOTIVASI BELAJAR PESERTA DIDIK - Manalu, Mega Susanty; Franky A.M. Lumbantobing,; Murni, (Prosiding Seminar Nasional Pendidikan IPA, 2025)
The learning process in schools currently is still teacher-centered by applying a traditional approach. The learning carried out does not create exciting, interactive and unique learning. The way to improve students' cognitive learning outcomes was using the LABIRIN approach (exciting, interactive, unique-based learning). The aim of this research are (a) to get an increase in the cognitive learning outcomes of participants in vibration and wave material for class VIII students at SMPN 2 Pagedangan after being taught using the LABIRIN approach, (b) to get an idea of ​​the difference in N-Gain in increasing cognitive learning outcomes between the experimental group and the control group , (c) get an overview of the differences in learning motivation between the experimental group and the control group after being given different treatments. This research used a quantitative method with a quasi-experimental design which was carried out in the experimental group VIII 1 and the control group VIII 3 in one of the junior high schools in Tangerang district in the even semester of 2023/2024. The instruments used are tests and questionnaires. The results of research data analysis show that; (a) The LABIRIN approach can improve the cognitive learning outcomes of class VIII students at SMP Negeri 2 Pagedangan on vibration and wave material, (b) The cognitive learning outcomes of students taught using the LABIRIN approach are higher than those of the group taught using the traditional approach. (c) Students who are taught using the LABIRIN approach have high learning motivation. Based on the results of data analysis calculations using the t test with a significance level of α= 5%, the values ​​obtained are tcount=2.034 and tcount=1.998, meaning reject H0 and accept Ha. Based on the results of data analysis, there is a difference in the increase in cognitive learning outcomes of students after being taught using the LABIRIN approach compared to using a traditional approach